Effect of microstructure and internal stress on hydrogen absorption into Ni thin film electrodes during alkaline water electrolysis. (20th April 2020) - Delvaux, Adeline; Lumbeeck, Gunnar; Idrissi, Hosni; Proost, Joris
Abstract: Efforts to improve the cell efficiency of hydrogen production by water electrolysis continue to address the electrochemical kinetics of the oxygen and hydrogen evolution reactions in detail. The objective of this work is to study a parasitic reaction occurring during the hydrogen evolution reaction (HER), namely the absorption of hydrogen atoms into the bulk electrode. Effects of the electrode microstructure and internal stress on this reaction have been addressed as well in this paper. Ni thin film samples were deposited on a Si substrate by sputter deposition with different deposition pressures, resulting in different microstructures and varying levels of internal stress. These microstructures were first analyzed in detail by Transmission Electron Microscopy (TEM). Cathodic chrono-amperometric measurements and cyclic voltammetries have then been performed in a homemade electrochemical cell. These tests were coupled to a multi-beam optical sensor (MOS) in order to obtain in-situ curvature measurements during hydrogen absorption. Indeed, since hydrogen absorption in the thin film geometry results in a constrained volume expansion, internal stress generation during HER can be monitored by means of curvature measurements. Our results show that different levels of internal stress, grain size and twin boundary density can be obtained by varying the deposition parameters. From an electrochemical point of view, this paper highlights the fact that the electrochemical surface mechanisms during HER are the same for all the electrodes, regardless of their microstructure. However it is shown that the absolute amount of hydrogen being absorbed into the Ni thin films increases when the grain size is reduced, due to a higher grain boundaries density which are favourite absorption sites for hydrogen. At the same time, it was concluded that H2 evolution is favoured at electrodes having a more compressive (i.e. a less tensile) internal stress. Finally, the subtle effect of microstructure on the hydrogen absorption rate will be discussed as well.